Oral Cancer Knowledge, Attitude, and Practice of Dentists in the State of Qatar - Diana H. Jboor (11506574) (2019)
Objectives: The aim of this study was to assess existing knowledge on oral cancer (OC), attitude toward OC examination, and clinical practice among dentists practicing in the governmental health sector in the State of Qatar, including the influence of personal characteristics. Materials and Methods: All 271 dentists practicing in Primary Health Care Centers (PHCC) and the Hamad Medical Corporation (HMC) were invited to participate in this cross-sectional study. Of these, 177 completed a self-administered, 48-item questionnaire. Based on the responses, knowledge of the risk factors for and clinical presentation of OC was categorized as high, medium, or low, and then further separated into satisfactory (medium/high) and unsatisfactory (low). Information on attitudes toward OC examination and clinical practice was also taken from the questionnaire. Results: The mean score for knowledge of the clinical presentation of OC was 7.59 (standard deviation [SD] = 2.40) out of 14. The mean score for knowledge of the risk factors for OC was 8.96 (SD = 2.31) out of 16. Dentists with ≤10 years of experience were more likely to have satisfactory knowledge of OC compared to dentists with >15 years of experience. Attending a continuous professional development (CPD) course on OC showed a trend with satisfactory clinical knowledge, although it was not statistically significant. Conclusion: This study identified gaps in dentists’ knowledge of OC; dentists demonstrated unsatisfactory knowledge of the clinical presentation of and risk factors for OC. The findings highlighted the need for educational interventions on OC, which are essential to improving health care outcomes and delivery of care. Other Information Published in: Dentistry Journal License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/dj7020043